Epidemiological profile of infant deaths from hemangioma and lymphangioma in Brazil (Research, Society and Development, 2022)
Objective: To evaluate the epidemiological profile of childhood deaths from hemangioma and lymphangioma in Brazil. Methodology: This is a descriptive, quantitative study, based on data of infant deaths and births according to hemangioma and lymphangioma, from the Department of Informatics of the Unified Health System between 2010 and 2019. Results: The female sex, deaths in the post-neonatal period and white race/color predominated in the national territory. During this period, the proportions of infant mortality related to hemangiomas and lymphagiomas decreased. However, the isolated analysis of macro-regions evidenced that the rates increased in 2019, when compared to the previous ones, especially in the North region, which had the highest infant mortality rates in the period studied. Conclusion: A better investigation of the linear decay in the mortality rates was not possible due to the fluctuation in the records, that may reflect the lack of notification in some regions, which reinforces the need for correct notification for the adoption of effective measures to reduce infant deaths from hemangioma and lymphangioma across Brazil.